Exercise intervention in people with cancer undergoing neoadjuvant cancer treatment and surgery: A systematic review. Issue 1 (January 2016) - Loughney, L.; West, M.A.; Kemp, G.J.; Grocott, M.P.W.; Jack, S.
Abstract: Background: Neoadjuvant cancer treatment decreases physical fitness. Low levels of physical fitness are associated with poor surgical outcome. Exercise training can stimulate skeletal muscle adaptations, such as increased mitochondrial content and improved oxygen uptake capacity that may contribute to improving physical fitness. This systematic review evaluates the evidence in support of exercise training in people with cancer undergoing the "dual hit" of neoadjuvant cancer treatment and surgery. Methods: We conducted a systematic database search of Embase Ovid, Ovid Medline without Revisions, SPORTDiscus, Web of Science, Cochrane Central Register of Controlled Trials Library andClinicalTrials.gov to identify trials addressing the effect of exercise training in people scheduled for neoadjuvant cancer treatment and surgery. Data extraction and analysis were based on a pre-defined plan. Results: The database search yielded 6489 candidate abstracts. Ninety-four references included the required terms. Four studies were eligible for inclusion (breast cancer, locally advanced rectal cancer). All studies reported that exercise training was safe and feasible and that adherence rates were acceptable (66–96%). In-hospital exercise training improves physical fitness however the impact on HRQoL and other clinical important outcomes was uncertain. Conclusion: This is the first systematic review of the effects of exercise training in people scheduled for "dual-hit" treatment. This evidence synthesis indicates that this approach is safe and feasible but that there are insufficient controlled trials in this area to draw reliable conclusions about the efficacy of such an intervention, the optimal characteristics of the intervention, or the impact on clinical or patient reported outcomes.